Institutional and matrix support and its relationship with primary healthcare - Alaneir de Fátima dos Santos; Antônio Thomaz Gonzaga da Matta Machado; Clarice Magalhães Rodrigues dos Reis; Daisy Maria Xavier Abreu; Lucas Henrique Lobato de Araújo; Simone Cristina Rodrigues; Ângela Maria de Lourdes Dayrell de Lima; Alzira de Oliveira Jorge; Délcio Fonseca Sobrinho (Universidade de São Paulo, 2015)
OBJECTIVE To analyze whether the level of institutional and matrix support is associated with better certification of primary healthcare teams. METHODS In this cross-sectional study, we evaluated two kinds of primary healthcare support - 14,489 teams received institutional support and 14,306 teams received matrix support. Logistic regression models were applied. In the institutional support model, the independent variable was "level of support" (as calculated by the sum of supporting activities for both modalities). In the matrix support model, in turn, the independent variables were the supporting activities. The multivariate analysis has considered variables with p < 0.20. The model was adjusted by the Hosmer-Lemeshow test. RESULTS The teams had institutional and matrix supporting activities (84.0% and 85.0%), respectively, with 55.0% of them performing between six and eight activities. For the institutional support, we have observed 1.96 and 3.77 chances for teams who had medium and high levels of support to have very good or good certification, respectively. For the matrix support, the chances of their having very good or good certification were 1.79 and 3.29, respectively. Regarding to the association between institutional support activities and the certification, the very good or good certification was positively associated with self-assessment (OR = 1.95), permanent education (OR = 1.43), shared evaluation (OR = 1.40), and supervision and evaluation of indicators (OR = 1.37). In regards to the matrix support, the very good or good certification was positively associated with permanent education (OR = 1.50), interventions in the territory (OR = 1.30), and discussion in the work processes (OR = 1.23). CONCLUSIONS In Brazil, supporting activities are being incorporated in primary healthcare, and there is an association between the level of support, both matrix and institutional, and the certification result.